A Further Validation of the Cognitive Bias Modification Effect on Trust in Middle Childhood. Issue 6 (November 2019) - Bosmans, Guy; Verhees, Martine W.F.T.; De Winter, Simon
Abstract: Recent middle childhood research suggests that children's trust in maternal support can be manipulated using Cognitive Bias Modification (CBM) aimed at changing children's interpretation of ambiguous maternal support-related behavior. The current study with 60 children (40 girls, M age = 10.62, SD age = 1.20) aimed to replicate previous research and to test whether the CBM effect is specific to trust or generalizes to other child evaluations of maternal behavior. More specifically, CBM effects on children's evaluation of parenting behavior were tested. Trust and maternal parenting behaviors were assessed using children's self-report. Results largely replicated previous findings, including the positive effect of CBM on children's trust in maternal support. Suggesting that this effect was specific for trust, the CBM manipulation did not affect children's appraisal of maternal parenting behavior. This finding supports the validity of CBM effects. Highlights: Trust in maternal support is linked with a positive interpretation bias This bias can be manipulated using Cognitive Bias Modification (CBM) CBM has a significant effect on children's trust in maternal support The CBM effect is specific for the expectations linked with the targeted bias